Time in range measurements for hyperglycemia management during pregnancy - Wang, Shuang; Xin, Hui; Li, Ling; Li, Ping (Clinica chimica acta, 2022)
•Increased blood glucose levels are associated with adverse pregnancy outcomes.•Indicators of blood glucose levels in hyperglycemic pregnancies should be evaluated.•Time-in-range (TIR) significance in pregnancy hyperglycemia management was reviewed.•Methods for measuring TIR were studied. The prevalence of adverse pregnancy outcomes associated with poor glycemic control are increasing. Accordingly, effective blood glucose monitoring during pregnancy has become a subject of intense interest. Continuous glucose monitoring (CGM) displays dynamic changes in blood glucose by using probes to measure glucose concentration in the interstitial fluid, and the rapid development of CGM has enabled the investigation of time in range (TIR) in the glucose target range as a new parameter to evaluate blood glucose. International guidelines have identified TIR as an important blood glucose assessment method for pregnant patients with type 1 diabetes mellitus that overcomes the limitations of conventional gestational blood glucose monitoring, better reflects fluctuation in blood glucose during pregnancy, and effectively improves maternal and neonatal outcomes. However, there is little clinical evidence for the use of TIR in pregnant women with gestational diabetes mellitus and those with pre-pregnant type 2 diabetes mellitus. TIR is expected to become a critical indicator of blood glucose control and management in hyperglycemic pregnant patients. We review the research progress of TIR to help clinicians understand the field of blood glucose monitoring in pregnant women with hyperglycemia.